Answer:
5:33. Simplified version: 1:6.6
Step-by-step explanation:
Hope this helps!
For this case, the first thing we must do is define variables:
x: number of quarters
y: number of nickels
We now write the system of equations:
x + y = 68
0.25x + 0.05y = 13.40
Solving the system we have:
x = 50
y = 18
Answer:
they have:
quarters = 50
nickels = 18
Answer:17
Step-by-step explanation:
Answer:
Radius: ![r =\frac{\sqrt {21}}{6}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%20%7B21%7D%7D%7B6%7D)
![Center = (-\frac{3}{2}, -\frac{2}{3})](https://tex.z-dn.net/?f=Center%20%3D%20%28-%5Cfrac%7B3%7D%7B2%7D%2C%20-%5Cfrac%7B2%7D%7B3%7D%29)
Step-by-step explanation:
Given
![9x^2 + 9y^2 + 27x + 12y + 19 = 0](https://tex.z-dn.net/?f=9x%5E2%20%2B%209y%5E2%20%2B%2027x%20%2B%2012y%20%2B%2019%20%3D%200)
Solving (a): The radius of the circle
First, we express the equation as:
![(x - h)^2 + (y - k)^2 = r^2](https://tex.z-dn.net/?f=%28x%20-%20h%29%5E2%20%2B%20%28y%20-%20k%29%5E2%20%3D%20r%5E2)
Where
![r = radius](https://tex.z-dn.net/?f=r%20%3D%20radius)
![(h,k) =center](https://tex.z-dn.net/?f=%28h%2Ck%29%20%3Dcenter)
So, we have:
![9x^2 + 9y^2 + 27x + 12y + 19 = 0](https://tex.z-dn.net/?f=9x%5E2%20%2B%209y%5E2%20%2B%2027x%20%2B%2012y%20%2B%2019%20%3D%200)
Divide through by 9
![x^2 + y^2 + 3x + \frac{12}{9}y + \frac{19}{9} = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%20y%5E2%20%2B%203x%20%2B%20%5Cfrac%7B12%7D%7B9%7Dy%20%2B%20%5Cfrac%7B19%7D%7B9%7D%20%3D%200)
Rewrite as:
![x^2 + 3x + y^2+ \frac{12}{9}y =- \frac{19}{9}](https://tex.z-dn.net/?f=x%5E2%20%20%2B%203x%20%2B%20y%5E2%2B%20%5Cfrac%7B12%7D%7B9%7Dy%20%3D-%20%5Cfrac%7B19%7D%7B9%7D)
Group the expression into 2
![[x^2 + 3x] + [y^2+ \frac{12}{9}y] =- \frac{19}{9}](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%5D%20%2B%20%5By%5E2%2B%20%5Cfrac%7B12%7D%7B9%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D)
![[x^2 + 3x] + [y^2+ \frac{4}{3}y] =- \frac{19}{9}](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%5D%20%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D)
Next, we complete the square on each group.
For ![[x^2 + 3x]](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%5D)
1: Divide the ![coefficient\ of\ x\ by\ 2](https://tex.z-dn.net/?f=coefficient%5C%20of%5C%20x%5C%20by%5C%202)
2: Take the ![square\ of\ the\ division](https://tex.z-dn.net/?f=square%5C%20of%5C%20the%5C%20division)
3: Add this ![square\ to\ both\ sides\ of\ the\ equation.](https://tex.z-dn.net/?f=square%5C%20to%5C%20both%5C%20sides%5C%20of%5C%20the%5C%20equation.)
So, we have:
![[x^2 + 3x] + [y^2+ \frac{4}{3}y] =- \frac{19}{9}](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%5D%20%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D)
![[x^2 + 3x + (\frac{3}{2})^2] + [y^2+ \frac{4}{3}y] =- \frac{19}{9}+ (\frac{3}{2})^2](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%20%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2%5D%20%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2)
Factorize
![[x + \frac{3}{2}]^2+ [y^2+ \frac{4}{3}y] =- \frac{19}{9}+ (\frac{3}{2})^2](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2)
Apply the same to y
![[x + \frac{3}{2}]^2+ [y^2+ \frac{4}{3}y +(\frac{4}{6})^2 ] =- \frac{19}{9}+ (\frac{3}{2})^2 +(\frac{4}{6})^2](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%20%2B%28%5Cfrac%7B4%7D%7B6%7D%29%5E2%20%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2%20%2B%28%5Cfrac%7B4%7D%7B6%7D%29%5E2)
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =- \frac{19}{9}+ (\frac{3}{2})^2 +(\frac{4}{6})^2](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2%20%2B%28%5Cfrac%7B4%7D%7B6%7D%29%5E2)
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =- \frac{19}{9}+ \frac{9}{4} +\frac{16}{36}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%5Cfrac%7B9%7D%7B4%7D%20%2B%5Cfrac%7B16%7D%7B36%7D)
Add the fractions
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =\frac{-19 * 4 + 9 * 9 + 16 * 1}{36}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D%5Cfrac%7B-19%20%2A%204%20%2B%209%20%2A%209%20%2B%2016%20%2A%201%7D%7B36%7D)
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =\frac{21}{36}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D%5Cfrac%7B21%7D%7B36%7D)
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =\frac{7}{12}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D%5Cfrac%7B7%7D%7B12%7D)
![[x + \frac{3}{2}]^2+ [y +\frac{2}{3}]^2 =\frac{7}{12}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B2%7D%7B3%7D%5D%5E2%20%3D%5Cfrac%7B7%7D%7B12%7D)
Recall that:
![(x - h)^2 + (y - k)^2 = r^2](https://tex.z-dn.net/?f=%28x%20-%20h%29%5E2%20%2B%20%28y%20-%20k%29%5E2%20%3D%20r%5E2)
By comparison:
![r^2 =\frac{7}{12}](https://tex.z-dn.net/?f=r%5E2%20%3D%5Cfrac%7B7%7D%7B12%7D)
Take square roots of both sides
![r =\sqrt{\frac{7}{12}}](https://tex.z-dn.net/?f=r%20%3D%5Csqrt%7B%5Cfrac%7B7%7D%7B12%7D%7D)
Split
![r =\frac{\sqrt 7}{\sqrt 12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%207%7D%7B%5Csqrt%2012%7D)
Rationalize
![r =\frac{\sqrt 7*\sqrt 12}{\sqrt 12*\sqrt 12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%207%2A%5Csqrt%2012%7D%7B%5Csqrt%2012%2A%5Csqrt%2012%7D)
![r =\frac{\sqrt {84}}{12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%20%7B84%7D%7D%7B12%7D)
![r =\frac{\sqrt {4*21}}{12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%20%7B4%2A21%7D%7D%7B12%7D)
![r =\frac{2\sqrt {21}}{12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B2%5Csqrt%20%7B21%7D%7D%7B12%7D)
![r =\frac{\sqrt {21}}{6}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%20%7B21%7D%7D%7B6%7D)
Solving (b): The center
Recall that:
![(x - h)^2 + (y - k)^2 = r^2](https://tex.z-dn.net/?f=%28x%20-%20h%29%5E2%20%2B%20%28y%20-%20k%29%5E2%20%3D%20r%5E2)
Where
![r = radius](https://tex.z-dn.net/?f=r%20%3D%20radius)
![(h,k) =center](https://tex.z-dn.net/?f=%28h%2Ck%29%20%3Dcenter)
From:
![[x + \frac{3}{2}]^2+ [y +\frac{2}{3}]^2 =\frac{7}{12}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B2%7D%7B3%7D%5D%5E2%20%3D%5Cfrac%7B7%7D%7B12%7D)
and ![-k = \frac{2}{3}](https://tex.z-dn.net/?f=-k%20%3D%20%5Cfrac%7B2%7D%7B3%7D)
Solve for h and k
and ![k = -\frac{2}{3}](https://tex.z-dn.net/?f=k%20%3D%20-%5Cfrac%7B2%7D%7B3%7D)
Hence, the center is:
![Center = (-\frac{3}{2}, -\frac{2}{3})](https://tex.z-dn.net/?f=Center%20%3D%20%28-%5Cfrac%7B3%7D%7B2%7D%2C%20-%5Cfrac%7B2%7D%7B3%7D%29)